Small, N-Terminal Tags Activate Parkin E3 Ubiquitin Ligase Activity by Disrupting Its Autoinhibited Conformation - Burchell, Lynn; Chaugule, Viduth K.; Walden, Helen (PLOS ONE, 2012)
Parkin is an E3 ubiquitin ligase, mutations in which cause Autosomal Recessive Parkinson's Disease. Many studies aimed at understanding Parkin function, regulation and dysfunction are performed using N-terminal epitope tags. We report here that the use of small tags such as FLAG, cMyc and HA, influence the physical stability and activity of Parkin in and out of cells, perturbing the autoinhibited native state of Parkin, resulting in an active-for-autoubiquitination species.